Location Quotient and Fuzzy ARAS in Determining Superior Commodities in the Food Crops Subsector - Melinda Aprianingsih; Ismail Husein (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
The selection of superior food crop commodities at the regional level is very important to sup-port agricultural development policies, but it is often carried out without comprehensive strategic analysis, risking less accurate decisions. The objective of this research is to establish the superior commodities of the food crop subsector in Langkat Regency based on regional contributions and a number of strategic criteria. The methods used include Location Quotient (LQ) to measure the region's comparative advantage based on production contribution, as well as Fuzzy ARAS to evaluate seven commodities based on ten strategic criteria with expert assessment using triangular fuzzy numbers. The results show that rice is the base commodity in 13 districts and has the highest contribution distribution. However, soybeans have become the superior commodity with the highest relative utility value (1.029), followed by cassava (1.015) and rice (0.983). The LQ and Fuzzy ARAS methods have proven effective in supporting the de-termination of superior commodities based on local potential.